The Effectiveness of Using Exit Slips on Improving EFL Learners’ Writing Ability and Reading Comprehension - Muhammad Fajri Hamdy; Linati Marta Kalisah (Nalar Global, 2020)
This study aimed to find out the effectiveness of using Exit Slips on learners' writing ability and reading comprehension improvement through deep investigation on its effect and the extent of its effect on both language skills by applying Quasi-Experimental research (pretest and post-test design) at an Islamic university’s language center (LC). Based on their similar characteristics, two EFL level II classrooms containing 60 learners were selected as sample. Furthermore, they were assigned to the experimental and the control group. In collecting the data, writing and reading tests, observations, and interviews were utilized to assess participants’ abilities prior to and after the treatment. In analyzing the data, the t-tests (paired and independent sample) were run in SPSS. In addition, Cohen D formula was applied to determine the effect size. The results demonstrated that students of the experimental group outperformed the control group after the treatment (p<0.05). In addition, the values of effect size obtained, writing (1.8) and reading (1.9), were categorized into strong effect size. Thus, Exit slip had significantly affected students’ writing ability and reading comprehension strongly to the extent that average students in the experimental group improved their ability of these two skills to match the student ranked first in the control group. It was due to exposure to summarization and paraphrasing, students’ motivation, and teacher’s creativity and feedback provided by the practice of Exit slip that affected students’ improvement. However, there was little evidence to conclude that which of the three mentioned factors in the practice of Exit slip dominantly affected the students’ improvement.